The Effect Atraining Program on Developing Self-Censorship Among Kindergarten Children - Issa AL-Fraidawi, Wafaa Hasan (Opción, 2019)
In light of the openness, technological advancement, and control of the me- dia and its means, such as satellite channels, and the availability of various communication devices such as mobile and iPad, which were shown in the hands of young people before adults and which negatively affected their lives and ways to satisfy their psychological needs, it resulted in a major change in values and the creation of a conflict between adhering to these values or giving them up, and to instill Self-censorship, developing and training our children on it, and enhancing the value of God Almighty’s observation in every move- ment. This is done by building a training program to help educators and fam- ilies to develop self-censorship among their children .. Accordingly, the cur- rent research problem was determined by answering the following question: - Does the training program have an impact on developing self-censorship among kindergarten children? The research sample consisted of (40) children in the kindergarten buds, (20) children in the experimental group and (20) children in the control group, to achieve the goal of the research. A measure of self-monitoring was prepared for kindergarten children and after reviewing the literature and previous studies, the researcher identified (25) paragraphs Each paragraph of the scale included two choices that the mothers of children answered for their children on the paragraphs of the scale, the stability was extracted by way of re-testing on the stability sample of (30) children and the stability factor of the test method was (890), which is an appropriate stability value and morally significant, after having The program was applied to the ex- perimental group, the researcher returned Baiq self control test on the experi- mental and control groups has been shown there are significant differences be- tween the two groups in favor of the experimental group, ie the impact of the training program in the development of self-censorship among the children of the experimental group.